1999
DOI: 10.1080/10406639908020608
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Hemoglobin and Serum Albumin Adducts of Benzo[a]Pyrene by Gas Chromatography-Mass Spectrometry in Humans and Their Relation to Exposure and to other Biological Markers

Abstract: In this study we have examined the relationship of benzo[a]pyrene (B[a]P) exposure with B[a]P-7,8-diol-9,10-epoxide (BPDE) adduct formation in globin and serum albumin (SA). We also have evaluated the relationship of BPDE-globin and -SA adduct formation with urinary 1 -hydroxypyrene ( 1 -OH-pyrene), and bulky DNA adducts in peripheral blood lymphocytes. The study groups consist of male Hungarian garage mechanics (smokers and nonsmokers) exposed to diesel engine exhaust and matched control samples from a blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The findings of much lower level of BPDE-His in SA compared to the BPDE-dG level in DNA is compatible with similar indications in the literature from the quantification of adduct levels by less specific methods. SA adducts measured by GC/MS as tetrols of BPDE released after acid hydrolysis and DNA adducts measured by 32 P-post labelling showed a ratio of SA to DNA adduct levels of 1:250 in a study of garage mechanics (Melikian et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The findings of much lower level of BPDE-His in SA compared to the BPDE-dG level in DNA is compatible with similar indications in the literature from the quantification of adduct levels by less specific methods. SA adducts measured by GC/MS as tetrols of BPDE released after acid hydrolysis and DNA adducts measured by 32 P-post labelling showed a ratio of SA to DNA adduct levels of 1:250 in a study of garage mechanics (Melikian et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, pyrene, which is a dominant compound in the PAH mixture at a concentration of f50 to 270 ng/cigarette in mainstream smoke, is mainly metabolized to the intermediary 1-OH-P, which forms predominantly 1-OH-P-gluc and, to much smaller extent, a sulfate conjugate, all of which are excreted in urine (35). Because the introduction of the urinary 1-OH-P as a biomarker of human PAH exposure, many studies have confirmed that 1-OH-P is a valid and sensitive indicator of PAH exposure (36,37). The correlation between BaP exposure from mainstream cigarette smoke and urinary 1-OH-P in the current study is r = 0.48 (n = 231).…”
Section: Cancer Epidemiology Biomarkers and Prevention 1413mentioning
confidence: 99%